PEMBERIAN PENYULUHAN TENTANG HIV AIDS PADA REMAJA DI SMAN 6 KEDIRI - Erda Restiya Agustin; Neta Ayu Andera; Lailaturohmah; Anik Nuridayanti (ADIMASKA (JURNAL PENGABDIAN MASYARAKAT KESEHATAN), 2025)
HIV AIDS is very important, especially for teenagers because a lack of knowledge about HIV AIDS can lead to cases. Preliminary studies at SMAN 6 Kediri had never provided audio-visual counseling to teenagers. The aim of this community service is to determine the level of understanding of teenagers about HIV AIDS at SMAN 6 Kediri. The methods used include health education about HIV AIDS to teenagers at SMAN 6 Kediri. The results of the activity showed that there was an increase in teenagers' knowledge about HIV AIDS after being given counseling. The conclusion of this activity shows that providing HIV AIDS education to teenagers at SMAN 6 Kediri has a big influence on understanding about the problem of HIV AIDS in teenagers. Therefore, this community service activity has great benefits, especially for teenagers at SMAN 6 Kediri